2015
DOI: 10.1182/blood-2015-01-621375
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of transformed follicular lymphoma in the modern era: a report from the National LymphoCare Study (NLCS)

Abstract: Key Points• The median posttransformation survival of 5 years suggests improved outcomes for transformed FL in the modern era.• Five-year progression-free and overall survival (66% and 88%) are favorable for patients with evidence of transformation at diagnosis.We assessed the incidence, prognostic features, and outcomes associated with transformation of follicular lymphoma (FL) among 2652 evaluable patients prospectively enrolled in the National LymphoCare Study. At a median follow-up of 6. , 83-86). The med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
170
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(202 citation statements)
references
References 30 publications
(56 reference statements)
16
170
2
6
Order By: Relevance
“…28 A number of groups have more recently reported on the rate of histologic transformation, and a consensus emerged that the rate was not clearly affected by type of treatment. 29 Recent estimates suggest that the rate of histologic transformation may be 2% to 3% per year. [29][30][31] However, the explanation for the lower incidence remains unclear.…”
Section: Incidence Of Transformation To Diffuse Large B-cell Lymphomamentioning
confidence: 99%
“…28 A number of groups have more recently reported on the rate of histologic transformation, and a consensus emerged that the rate was not clearly affected by type of treatment. 29 Recent estimates suggest that the rate of histologic transformation may be 2% to 3% per year. [29][30][31] However, the explanation for the lower incidence remains unclear.…”
Section: Incidence Of Transformation To Diffuse Large B-cell Lymphomamentioning
confidence: 99%
“…The OS at five years was 50%, and the data demonstrate that patients with synchronous transformation of FL had outcomes comparable to FL without transformation (five-year OS of 88%). 2 The NCCN study observed that younger chemotherapy-naive or rituximab-naive patients had a favorable outcome without transplantation with the five-year OS of 80%.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, the median overall survival (OS) has improved from one year to approximately five years. 2 New modalities of therapy and earlier diagnosis of histological transformation (HT) could be the attributing factors. Due to the aggressive nature of transformed lymphomas (TLs), many centers offer high-dose chemotherapy and autologous stem cell transplantation (HD-ASCT) to eligible patients with chemotherapy-sensitive disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First-line treatment for patients with DLBCL, PMBCL, or TFL generally consists of combination therapy with rituximab and chemotherapy [13,19,20]. Most new cases of DLBCL are cured with standard of care frontline therapy, but 10-15% of patients experience primary refractory disease and 20-30% of patients who do respond to front-line treatment will relapse [13].…”
Section: Epidemiology and Treatment Of Aggressive B Cell Lymphomasmentioning
confidence: 99%